Pengukuran Kualitas Aset Taman Plaza Rakyat di Lingkungan Kantor Pemerintahan Kota Cimahi - Hasna, Amelia; Suciyani, Wida Oktavia (Jurnal Lanskap Indonesia, 2024)
Taman Plaza Rakyat is one of the Green Open Spaces (RTH) managed by Dinas Perumahan dan Kawasan Pemukiman, Dinas Lingkungan Hidup, Dinas Pekerjaan Umum dan Penataan Ruang of Cimahi City. This park is designed as a public green open space that can be used for people in Cimahi City. Based on preliminary observations, there are several problems that exist in the park. The purpose are to determine the quality of asset Taman Plaza Rakyat based on 5 aspects among other are accessibility, attractiveness and appeal, comfort, activity and use, also safety and security (Public Space Quality Evaluation, Praliya and Garg 2019). The second is to find the solutions to solve the problems. The type of research is descriptive method with qualitative and quantitative approaches. Data collection techniques used are observation, interviews, questionnaires with 100 respondents, and documentation studies. The results of asset quality evaluation is enough but there are lack of facilities and amenities in the park. The park lack of facilities in five dimention among others are accessibility, attractiveness and appeal, comfort, activity and use, as well as safety and security. Due to the result of asset quality evaluation, Taman Plaza Rakyat need to be improved by asset development planning to increase the quality of the park